Polydopamine Induced Wettability Switching of Cellulose Nanofibers/n-Dodecanethiol Composite Aerogels - Runan Gao; Ying Shang; Peng Jiao; Yue Jiao; Jian Li; Yun Lu (International Journal of Polymer Science)
The novel wettability switchable cellulose nanofiber- (CNF-) based aerogel was conveniently prepared by polydopamine mediated composition of CNF and n-dodecanethiol. The wettability of aerogels can be controlled by adjusting the PDA and n-dodecanethiol loading content, which leads to a variation of water contact angle from 0-149°. The PDA was coated on cellulose nanofibers via hydrogen bonds and then n-dodecanethiol was anchored onto the scaffolds by Michael addition reaction, which was revealed by XPS and FTIR spectra. The composite aerogel can selectively absorb a series of oily liquids from the oil/water mixture, with the maximum absorption capacity of 68 g/g. This work presented a facile strategy to prepare wettability switchable CNF-based heterogenous aerogel and exhibited the potential of the composite aerogel for oil/water separation.